THE EFFECT OF PROFITABILITY AND LEVERAGE ON FINANCIAL DISTRESS USING THE ALTMAN Z-SCORE MODEL: EVIDENCE FROM THE CONSUMER CYCLICALS SECTOR IN INDONESIA - Ummu Sulaim Hasanah; Muhammad Iqbal Pribadi; Rahman Anshari (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study aims to examine the effect of profitability and leverage on financial distress using the Altman Z-Score model in the consumer cyclicals sector in Indonesia for the 2021–2023 period. This research employs a quantitative approach with a causal-explanatory method. The population consists of 166 companies listed on the Indonesia Stock Exchange (IDX), with 101 companies selected as samples through purposive sampling based on specific criteria. The data used in this study are secondary data obtained from the companies’ financial reports. Profitability is measured by Return on Assets (ROA), leverage is measured by Debt to Equity Ratio (DER), and financial distress is measured using the Altman Z-Score. The analytical technique applied in this study is panel data regression using STATA 17 software. The results show that partially, profitability has a positive and significant effect on financial distress, while leverage has a negative and significant effect on financial distress.